Entrepreneurship: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
The study at hand explored the impact of practising environmental sustainability by South African SMEs on their firm performance. With a contemporary view, the study considered a multidimensional viewpoint by measuring firm performance through financial, customer satisfaction and employee satisfaction as constructs of firm performance. Herein, three hypotheses were postulated which stated that environmental sustainable development (ESD) was significantly and positively related to (1) financial performance (2) customer satisfaction performance and (3) employee satisfaction performance amongst SMEs in South Africa. A questionnaire was distributed in the month of August 2017 with a sample size of 222 participants being subsequently utilised. Convenience sampling method was employed and data was subsequently analysed with the structural equation modelling (SEM) being the primary technique. Descriptive statistics and factor analysis were also utilised in data analysis. Of the postulated hypotheses, all were supported. Thus, established in this study is that environmental sustainable development was significantly and positively associated to financial performance, customer satisfaction performance and employee satisfaction performance. Hence, recommendations are put forward for policy formulations that take cognisance of the multidimensionality of firm performance which is ideal for the future and contemporary sustainable development dispensation.